Dirac function and its applications in solving some problems in mathematics - Rehman Mohammed, Hisham (Journal of Al-Qadisiyah for Computer Science and Mathematics, 2017)
The paper presents various ways of defining and introducing Dirac delta function, its application in solving some problems and show the possibility of using delta-function in mathematics and physics.